Innovation Framework Towards Sustainability Supply Chain Management - Norlinda Mohd Rozar; Mohd Hazeem Sidik; Muhammad Ashlyzan Razik; Jagan Jeevan; Mohamad Rosni Othman; Mohd Saiful Izwaan Saadon; Saadi kamarudin (International Journal of Supply Chain Management, 2020)
Abstract: Sustainability is hinged on innovation. The importance of sustainable innovation management in sustainable supply chain management (SSCM) cannot be underestimated. Studies on SSCM have emphasised the need for sustainable innovation in achieving sustainability but none provides deep insights into sustainable innovation management in SSCM implementation in organisation. This lack of research depth stimulates this study to identify and investigate criteria for sustainable supply chain management innovation advancement. This paper proposes a sustainable innovation criteria framework in investigating sustainable supply chains in manufacturing companies. The results of the study will inform industrial managers, practitioners and decision-makers on which criteria to focus on during the implementation stage, to increase sustainability in manufacturing supply chains, and further advance corporate and supply chain sustainable development. The framework may also serve as a theoretical construct for a future empirical study on sustainable supply chain innovation in the manufacturing sector. This paper sets the stage for further research in sustainable innovation practices in the manufacturing sector and its supply chains. Keywords: Supply chain management, Sustainability, Innovation management